Absence of hydrogen peroxide production by or catalase action in Rickettsia prowazeki. - Myers, W F (1978)
Glutamic acid oxidation by Rickettsia prowazeki is not accompanied by hydrogen peroxide generation, nor is added hydrogen peroxide degraded, as measured by a manometric technique.